Laboratory Evaluation of a Plant-Produced High Polymer–Content Asphalt Mixture. Issue 1 (2017) - Bowers, Benjamin F.; Diefenderfer, Stacey D.; Diefenderfer, Brian K.
Reflective cracking in asphalt overlays placed over jointed concrete pavements is of major concern in Virginia, as well as nationally, and has generated interest in various reflective crack mitigation techniques that are easy to implement. One technique is the use of binder modifiers, such as asphalt rubber, polymer-modified asphalt binders, or high polymer–content (HP) modified binders. In the summer of 2014, the Virginia Department of Transportation placed an HP asphalt mixture produced by using an asphalt binder that contained approximately 7.5% styrene-butadiene-styrene polymer in a trial section within a subdivision as a low-risk means to assess constructability and laboratory performance. The HP mixture was evaluated in comparison with a typical surface asphalt mixture with a 9.5-mm nominal maximum aggregate size, as a control. Testing was performed on specimens fabricated from reheated control and HP mixture samples, as well as on specimens fabricated from site-compacted samples and road cores of the HP mixture. In addition, binder grading was performed on the control binder and modified binder. The HP binder was significantly more elastic than the control binder. Comparable dynamic moduli were found for reheated mixture specimens, although site-compacted and road core specimens from the HP mixture had lower stiffness than the control mixture. The HP mixture performed better in rutting and in fatigue. The Texas overlay test indicated similar crack resistance between the two mixtures; however, measured loads of the HP specimens were nearly half those of the control specimens. The results of laboratory testing indicated that the mixture incorporating the HP binder should have a far greater fatigue life and rut resistance than the control mixture.